2016
DOI: 10.1371/journal.pone.0150630
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Entrainment Patterns of Human Emotion in Social Media

Abstract: Emotion entrainment, which is generally defined as the synchronous convergence of human emotions, performs many important social functions. However, what the specific mechanisms of emotion entrainment are beyond in-person interactions, and how human emotions evolve under different entrainment patterns in large-scale social communities, are still unknown. In this paper, we aim to examine the massive emotion entrainment patterns and understand the underlying mechanisms in the context of social media. As modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…As social networks expand in size, a large number of human producers and consumers will become less reciprocal due to time displacement. In a study of over 1 million users and 18 million English blog posts on http://livejournal.com and 1.7 million users and 3.5 million messages on China's Sina Weibo, He, Zheng, Zeng, Luo, and Zhang () examined emotion entrainment, or the evolving synchronous convergence of expressed emotion in those messages. They found that, despite different patterns and lifespans between the two platforms, entrainment followed a consistent three‐stage process in which, initially, one person proactively entrained toward the other, at which point the individuals mutually entrained toward each other, and once the relationship was established, entrainment became more asymmetric again.…”
Section: Parameters Of Relational Spacementioning
confidence: 99%
“…As social networks expand in size, a large number of human producers and consumers will become less reciprocal due to time displacement. In a study of over 1 million users and 18 million English blog posts on http://livejournal.com and 1.7 million users and 3.5 million messages on China's Sina Weibo, He, Zheng, Zeng, Luo, and Zhang () examined emotion entrainment, or the evolving synchronous convergence of expressed emotion in those messages. They found that, despite different patterns and lifespans between the two platforms, entrainment followed a consistent three‐stage process in which, initially, one person proactively entrained toward the other, at which point the individuals mutually entrained toward each other, and once the relationship was established, entrainment became more asymmetric again.…”
Section: Parameters Of Relational Spacementioning
confidence: 99%
“…An important part of the selling process for wine is based on storytelling (Lamarre, 2018) about the wine-making process and the winemaker's history (Bach, 2017a), playing with emotive responsiveness of the clients; if the seller cannot activate this part or if clients break the emotional bond between them and the seller, the sale is more likely to be unsuccessful. At the same time, recent research has shown that analogical emotions and emotion contagion can be transferred into the virtual world (He et al, 2016).…”
Section: The Limits Of the Digital Languagementioning
confidence: 99%
“…The optimal set of factors can be extended to a number of emotions as well [2]. For example, the factors 1, 2, 3, and 4 are dominant for emotions 12,14,18,20,21,22 for K=7, indicating that 6 emotions (Affection, Contentment, Antic Pleasure Imagery, Relief, Surprise, and Suspense) can be detected with 7 factors, of which 1, 2, 3, and 4 (Electroencephalography, Heart rate, Heart rate variability, Pre-ejection period) are common for all [2].…”
Section: Most Dominant Factors (Mdf)mentioning
confidence: 99%
“…The detection of such emotional responses relies mainly on several vital factors such as Heart [1-3, 9, 10]. Human emotion detection models can be readily used in conjunction with social networks such as Facebook, Twitter, Myspace, LinkedIn, Instagram, and messenger applications, amongst others, by annunciating the emotional statuses between communicating parties [1,20]. Other suitable arenas would include health care applications readily disseminating vital health signs between patients and their care providers [1].…”
Section: Introductionmentioning
confidence: 99%